PENGARUH KEADILAN PROSEDURAL DAN KEADILAN INTERAKSIONAL TERHADAP PERILAKU RETALIASI KARYAWAN - Kusumawati, Yulia; Surya Putra, Made (E-Jurnal Manajemen, 2015)
Retaliation is a negative act committed employees resulting from the  perception of injustice by the company relating to a particular policy . Employee retaliation behavior can be minimized by pressing the contributing factors. One of the factors causes retaliation behavior is organizational justice. The study was conducted at Centro Lifestyle Department Store, Kuta-Bali, with a disproportionate random sampling method Sampling. The analysis finds that procedural justice and interactional justice has negative influence on  employee retaliation behavior. Management can reduce intentionality retaliation behavior of employees by providing training to each employee morale.
Keywords: Keadilan Prosedural; Keadilan Interaksional; Retaliasi